2012
DOI: 10.1007/s11270-012-1171-z
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Dependent and Culture-Independent Methods in Evaluation of Emission of Enterobacteriaceae from Sewage to the Air and Surface Water

Abstract: The number of Enterobacteriaceae, with particular attention given to the presence of Escherichia coli and Klebsiella pneumoniae, was determined in hospital effluents and municipal wastewater after various stages of purification. The emission of these microorganisms to the ambient air near wastewater treatment plant (WWTP) facilities and to the river water, which is a receiver of the WWTP effluent, was also studied using fluorescence in situ hybridization (FISH) and cultivation methods. The number of Enterobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Previous study showed that cell lysis of many gram-negative bacteria produces toxic lipopolysaccharides (LPS) called endotoxins also some strains like E. coli generate verotoxins, and heat-labile enterotoxins, that bring on immune responses [33]. Melbostad et al (1994) surveyed 12 participants from five different WWTP in East Norway.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study showed that cell lysis of many gram-negative bacteria produces toxic lipopolysaccharides (LPS) called endotoxins also some strains like E. coli generate verotoxins, and heat-labile enterotoxins, that bring on immune responses [33]. Melbostad et al (1994) surveyed 12 participants from five different WWTP in East Norway.…”
Section: Resultsmentioning
confidence: 99%
“…Enterobacter sp. was an important pathogenic bacterium that causes infectious diseases including skin soft tissue infection, respiratory infection, urinary tract infection, and sepsis because of the widespread use of antibiotics (Brodka et al 2012;Korzeniewska and Harnisz 2012). Future studies should focus more on the potential health risk of exposure to Acinetobacter, S. saprophyticus, and Enterobacter sp.…”
Section: Genetic Structure Of Airborne Bacterial Communitiesmentioning
confidence: 99%
“…The combined use of microscopy along with immunology or genetic methods allows identification to the species level. Fluorescence in situ hybridization may allow phylogenetic identification of bacteria (Amann et al, 1996;Korzeniewska and Harnisz, 2012). Electron microscopy has been used to enumerate smaller particles such as viruses and allows their classification based on their morphology (Hanssen et al, 2010;Kim et al, 2013;Whon et al, 2012;Yamaguchi et al, 2012).…”
Section: Microscopymentioning
confidence: 99%